Functional Mutations in 5′UTR of the BMPR2 Gene Identified in Chinese Families with Pulmonary Arterial Hypertension. (1st March 2016) - Wang, Jian; Zhang, Chenting; Liu, Chunli; Wang, Wei; Zhang, Nuofu; Hadadi, Cyrus; Huang, Junyi; Zhong, Nanshan; Lu, Wenju
Abstract : Pulmonary arterial hypertension (PAH) is a progressive pulmonary vasculopathy with significant morbidity and mortality. Bone morphogenetic protein receptor type 2 ( BMPR2 ) has been well recognized as the principal gene responsible for heritable and sporadic PAH. Four unrelated Chinese patients with PAH and their family members, both symptomatic and asymptomatic, were genetically evaluated by sequencing all exons and the flanking regions of BMPR2 . Functionality of the aberrant mutations at the 5′ untranslated region (UTR) of BMPR2 in the families with PAH was determined by site mutation, transient transfection, and promoter‐reporter assays. Four individual mutations in the BMPR2 gene were identified in the 4 families, respectively: 10‐GGC repeats, 13‐GGC repeats, 4‐AGC repeats in 5–UTR, and a novel missense mutation in exon 7 (c.961C>T; p.Arg321X). Moreover, we demonstrated that (1) these 5′UTR mutations decreased the transcription of BMPR2 and (2) the GGC repeats and AGC repeats in BMPR2 5′UTR bore functional binding sites of EGR‐1 and MYF5, respectively. This is the first report demonstrating the presence of functional BMPR2 5′UTR mutations in familial patients with PAH and further indicating that EGR‐1 and MYF5 are potential targets for correcting these genetic abnormalities for PAH therapy.